Integration Of Project-Based Learning (PJBL) Learning Model And Kahoot Media In Learning To Writing Argumentation Texts For Students Of Grade XI SMA Negeri 1 Tompaso - Nefie Rinda Lumintang; Sjuul Lendo; Justien RR Wuisang (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Abstract This study aims to improve the argumentative writing skills of eleventh-grade students at SMA Negeri 1 Tompaso through the integration of the Project Based Learning (PjBL) model and Kahoot media in learning to write argumentative texts. This research employed Classroom Action Research. The subjects of this study were 36 students of class XI at SMA Negeri 1 Tompaso. The research was conducted in two cycles, with each cycle consisting of four stages: planning, acting, observing, and reflecting. The data collection techniques used in this research included observation, interviews, argumentative writing tests, and documentation. The collected data were analyzed using descriptive qualitative and quantitative analysis techniques. The results of this study indicate that the implementation of the integration of the Project Based Learning (PjBL) model and Kahoot media can improve students' argumentative writing skills in terms of both process and product for the eleventh-grade students of SMA Negeri 1 Tompaso. The improvement in the quality of the learning process can be seen from the increased roles of both teachers and students in the learning activities. This improvement is reflected in the emergence of positive responses, such as cooperation, enthusiasm among students, and a more conducive learning atmosphere. The improvement in the learning process ultimately had a positive impact on the improvement of the learning product. The improvement in the product can be seen from the increase in students' argumentative writing scores from Cycle I to Cycle II. The average score in Cycle I was 63.55%, while in Cycle II it increased to 88.22%. The increase in the average score from Cycle I to Cycle II was 24.67%. improvement, learning, writing, argumentative text, Project Based Learning (PjBL).